Comparative Analysis of Protection Schemes for Shunt Reactors: Addressing Turn-to-Ground and Turn Faults with Parametric Sensitivity and Transient Evaluations - Maria Leonor Silva de Almeida; Diogo Guilherme Ferreira; Lina P. Garcés Negrete; Jesús M. López-Lezama; Nicolás Muñoz-Galeano (Energies)
In electrical power systems, shunt reactors control excess reactive power, keeping voltage levels within acceptable limits. As shunt reactors play a crucial role in the operation of electrical systems, it is essential to ensure the use of modern and fast protection schemes for these devices. Furthermore, protection functions must be capable of identifying various fault conditions, including critical operating situations such as turn-to-ground and turn faults, involving only a few short-circuited turns. This paper proposes a comparative evaluation of protection schemes commonly employed by manufacturers to meet the requirements of different grid codes. Thus, the investigation encompasses restricted earth fault, directional, differential, and distance functions. The latter is typically cited as a backup protection function. To support the analyses conducted, an electrical power system with shunt compensation was modeled in the ATPDraw software version 7.3. Through this platform, various internal fault conditions were simulated, encompassing turn-to-ground and turn faults. This facilitated the analysis of the influence of parameters such as the leakage factor value and the number of short-circuited turns. Additionally, external fault conditions were evaluated, including cases involving Current Transformer (CT) saturation.